Investigating the Necessity of an Ombudsman in Bangladesh - Tabassum, Nishat (Jurnal Administrasi Publik (Public Administration Journal), 2024)
An independent official tasked with investigating complaints made by citizens against public authorities or organizations is known as the Ombudsman. It is an essential mechanism for promoting accountability and transparency within government and public institutions, helping to restore public trust and ensure fair treatment of citizens. Article 77 of the Constitution of Bangladesh outlines the legal framework for establishing the office of the Ombudsman. The Ombudsman Act of Bangladesh, enacted in 1980, was established under the constitutional framework provided by Article 77. This study is based on solely secondary sources, and it is descriptive. This study has discussed that for protecting the rights of citizens, bridge the gap between government and citizens, and strengthen democratic principles, establishing the Ombudsman is mandatory in the present context of Bangladesh. This study has also discussed the loopholes in the Ombudsman Act of Bangladesh and what amendments should be introduced.